Psychological Distress Related to COVID-19 Among Nepalese Professionals: An Online Cross-sectional Study - Asraf, Hussain; Sandesh, Sawant; Mishra, Jeetendra; Ram, Ramji; pandey, Mahendra; Bista, Sagun; Sarraf, Pramod Kumar (Med Phoenix, 2020)
Background: COVID-19 is a highly infectious disease caused by SARS-CoV2 virus. It's psychological distress would be a major obstacle towards social normalcy to pre-COVID era. There were lacks of studies to assess these distresses. The aim of this study was to study psychological distress related to COVID-19 among Nepalese professionals. Methods: This online cross-sectional survey was conducted from 12th-20th, June-2020. Questionnaires were based on Corona-virus Anxiety Scale (CAS) and Obsession with COVID-19 scale (OCS). Results: Among 244 participants, majority were in the age group of 20-45 years with male female ratio of 2.1:1. About one third were health workers, 46% were teachers and service holders and remaining were from other professions. Majority of participants had subclinical obsessive (83.2%) and sub-clinical anxiety symptoms (69.3%). Law enforcement professionals (30.0%) and journalists 18.2% had highest prevalence of problematic obsessive symptoms. Law enforcement professionals (40%) had highest prevalence of problematic anxiety symptoms followed by health care workers (28.4%). About 35% of participants opted for multiple positive methods to cope with their obsessive and anxiety symptoms. Participants with higher obsession score had higher anxiety symptoms (r=0.592, p=<0.001). Conclusion: Majority of participants only had sub-clinical obsession and anxiety related to COVID. But, health workers, law enforcement and journalism professionals were having problematic symptoms. Thus, efforts need to be concentrated towards formulation of policies for safe and productive environment for these professionals.